Clear aligner treatment: different perspectives between orthodontists and general dentists - Fabrizia d'Apuzzo; Letizia Perillo; Caroline K. Carrico; Tommaso Castroflorio; Vincenzo Grassia; Steven J. Lindauer; Bhavna Shroff (SpringerOpen, 2019)
Abstract Purpose To evaluate differences between orthodontists and general dentists in experience with clear aligners (CA), patients' demand and perception, types of patients, and malocclusion treated with CA and to compare the two groups of clinicians not using CA in their practice. Methods A Web-based survey was developed and sent to the 129 members of the European Aligner Society and randomly to 200 doctors of dental surgery by e-mail. They responded on demographics and to one of two different parts for clinicians using CA or not using CA. Statistical analysis was performed with SAS EGv.6.1. Results The response rate was 74%. Among the total of respondents, the majority reported utilizing CA in their practice with a greater percentage of orthodontists (P = 0.0040). Overall, orthodontists learned more about CA during academic seminars comparing to general dentists, and they treated more class I with crowding (P = 0.0002) and with open bite (P = 0.0462). The majority of patients treated with CA were female and adults with a full-time employment, and the patients' knowledge about CA treatment was mainly provided by information from external media advertising. For respondents not using CA, orthodontists were more likely to report that CA limit treatment outcomes, whereas general practitioners were reported not having enough experience to use them. Conclusions There were some significant differences between orthodontists and general dentists mainly in experience and case selection for clinicians using CA as well as in the reasons provided for not using CA in their practice.